Influence of sowing time based temperature on flowering and seed yield of french bean (Phaseolus vulgaris L.) (SAARC Journal of Agriculture, 2017)
A field experiment was conducted at the research field of Agronomy Division, BARI, Joydebpur, Gazipur during rabi season of 2015-16 to evaluate the flowering behavior and seed yield of French bean. Three varieties viz., BARI Jharsheem-1, BARI Jharsheem-2 and BARI Jharsheem-3 were sown at 15 November, 30 November, 15 December and 30 December for getting temperature variation. Sowing dates based temperature variation, significantly affect the flowering behaviour and seed yield of French bean varieties. Flowering duration of 15 November and 30 November sowings were longer due to prevailing low temperatures (Min.11.72-13.240C and Max. 25.02-25.820C). On the contrary, minimum flowering duration was recorded in 30 December sown crop (11-17 days). Minimum duration might be due to prevailing high temperature (Min. 16.05-18.610C and Max. 28.89-31.310C) that shorten the flowering duration of all French bean varieties. November sowing performed better in relation to yield components and seed yield than other sowing. BARI Jharsheem-1 produced the maximum seed yield (1734 kg ha-1) in 15 November which was statistically similar to 30 November sowing (1620 kg ha-1). The lowest seed yield (421 kg ha-1) was produced in BARI Jharsheem -2 from 30 December sowing. The highest seed yield was obtained from November sowing might be due to favourable optimum temperature for better flowering and pod setting that resulted in maximum seed.SAARC J. Agri., 15(1): 77-84 (2017)